Exploring Anatomical Variations of the Brachiocephalic Artery and Their Clinical Significance: A Study Utilising Cadaveric Specimens - Nimisha Madhu; Chandra Kiran (Student's Journal of Health Research Africa, 2024)
Background: The brachiocephalic artery (BCA) is a critical vascular structure that streams blood to the right side of the head, neck, and upper limb. Anatomical variations in the BCA can significantly impact clinical practices, including surgical procedures, diagnostic imaging, and the management of vascular diseases. The study investigated the anatomical differences of the BCA and their clinical relevance through a comprehensive morphometric analysis using cadaveric specimens. Methods: 60 cadavers that had been embalmed with formalin were examined. Every cadaver's torso length was measured starting from the seventh cervical vertebra's spine and ending at the imaginary line that connects the iliac crests. The BCA was made visible by dissecting the thoracic area, and its length was determined from the point of origin to the points where it split into the right subclavian artery (RSA) and the right common carotid artery (RCCA). SPSS version 21.0 was used to analyse the data. Results: The mean torso length was 70.3 ± 5.6 cm, and the mean BCA length was 4.2 ± 0.8 cm. Variants of the BCA were categorized into three types: Type A (50%), Type B (33.3%), and Type C (16.7%). Variations in the origin of the BCA were observed, with the typical origin in 75% of cases, Variant Origin 1 in 16.7%, and Variant Origin 2 in 8.3%. A considerable positive correlation was found between torso length and BCA length (r = 0.68, p < 0.01). Conclusion: This study highlights the variability in BCA anatomy and its correlation with torso length. These findings have important implications for clinical and surgical practices, emphasizing the need for personalized approaches based on individual anatomical differences. Recommendations: Clinicians and surgeons should consider these anatomical variations during preoperative planning and diagnostic imaging to improve patient outcomes.